Comparative study of fungal growth inhibition by encapsulated fungicicde in multiwall carbon nanotubes (MWCNTs) and activated carbon - Norhafizah Hatta, 1994-, author 640441; Nur Izzati Mohd. Noh, 1987- supervisor 554028; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Biologi - Industri)) - Universiti Teknologi Malaysia, 2018